2011
DOI: 10.2147/ijn.s19561
|View full text |Cite
|
Sign up to set email alerts
|

The quest for targeted delivery in colon cancer: mucoadhesive valdecoxib microspheres

Abstract: The aim of the present study was to prepare valdecoxib, a cyclo-oxygenase-2 enzyme inhibitor, as a loaded multiparticulate system to achieve site-specific drug delivery to colorectal tumors. Film coating was done with the pH-sensitive polymer Eudragit S100 and sodium alginate was used as mucoadhesive polymer in the core. The microspheres were characterized by X-ray diffraction, differential scanning calorimetry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…19 The size of the resulting HCNPs, as measured by dynamic light scattering, averaged 171.10 ± 48.58 nm. The polydispersity index was 0.67.…”
Section: Cisplatin-hyaluronan Conjugate Nanoparticlesmentioning
confidence: 97%
See 1 more Smart Citation
“…19 The size of the resulting HCNPs, as measured by dynamic light scattering, averaged 171.10 ± 48.58 nm. The polydispersity index was 0.67.…”
Section: Cisplatin-hyaluronan Conjugate Nanoparticlesmentioning
confidence: 97%
“…Thakral et al used the natural polymer as a core and subsequently coated it with Eudragit S100 for colon targeting. 18,19 In our previous work, we successfully fabricated Eudragit S100-coated pectinate/alginate microspheres (PAMs) using an electrospray method and polyelectrolyte multilayer-coating technique in an aqueous solution, and demonstrated that cisplatin release from Eudragit S100-coated PAMs was retarded in simulated gastric conditions. 20 However, the new drug-delivery system only improved the efficiency of protecting drug activity.…”
Section: Introductionmentioning
confidence: 99%
“…The specific pH conditions of the colonic region were exploited to deliver the drug to the region, by developing a pHdependent system, using Eudragit S100 (22). Eudragit S100 is an anionic polymer synthesized from methacrylic acid and methyl methacrylate which dissolves in the region of the digestive tract where pH is >7 (23,24). The system was designed in such a manner that an acidic microenvironment is developed in colon after the release of the drug from the system, to arrest the hydrolysis of the lactone ring of CPT.…”
Section: Introductionmentioning
confidence: 99%
“…3 Similar observations have also been made in the management of colon cancer. 4,5 In fact, the deposition and adherence of fluorescent polystyrene particles were greater in the ulcerated regions of the inflamed tissue than in nonulcerated control tissue in experimental models of rodent colitis; this adhesion was size-dependent, the best results being obtained with particle sizes ranging from 25 to 100 nm. 3 Based on this paradigm, different groups have developed the delivery of several drugs, such as tacrolimus and rolipram, delivered on poly(lactic-co-glycolic acid) nanoparticles; dexamethasone on poly(d-lactide) particles; 3 or fluticasone propionate on hydroxypropyl betacyclodextrin.…”
mentioning
confidence: 99%